Viability assessment and estimation of the germination potential of charophyte oospores: testing for site and species specificity. Issue 1 (2nd January 2018) - Holzhausen, Anja; Porsche, Christian; Schubert, Hendrik
Abstract: Anthropogenic disturbance over several decades has caused aquatic ecosystems to deteriorate, raising concerns about their condition and, consequently, prompting restorative activities. The recovery of submerged vegetation (notably charophytes) is a crucial requirement for the restoration of eutrophic aquatic systems. The success of this action often depends on the availability and germinability of aquatic plant diaspores. To characterize the potential of the diaspore bank for the restoration of charophyte stands, we investigated viability, germination potential and conditions for dormancy breaking of the oospores in three independent studies. The viability of the oospores was determined by means of the triphenyltetrazolium chloride (TTC) test. The germination potential of the diaspore banks from seven locations was estimated for potential irradiance dependency and the impact of factors influencing the dormancy status was assessed. For the latter aspect, the germination experiments were conducted with solitary oospores from plants and diaspore banks, pretreated under different temperature and desiccation regimens. The results showed species-specific differences in dormancy breakage and germination of 10 charophyte species. Five of the species tested, Chara filiformis Hertzsch, Lychnothamnus barbatus (Meyen) Leonh., Tolypella glomerata (Desvaux) Leonh., Nitella mucronata (A.Braun) Miq. in Hall and Nitella flexilis (L.) C. Agardh/ Nitella opaca (C. Agardh ex Bruz.) C. Agardh, exhibited light-dependent germination. The irradiances where maximum germination was achieved correspond well to the species' distribution within the vertical irradiance gradient in their habitats.